International research collaboration: An emerging domain of innovation studies? - Chen, K; Zhang, Y; Fu, X (Elsevier, 2018)
International research collaboration (IRC) has been increasingly important as an emerging area of innovation studies. This study reviews the intellectual base, main research trajectories and intellectual communities of the IRC research domain over the period 1957–2015. It integrates qualitative review and three quantitative analyses including co-citation network analysis, main path analysis and bibliographic coupling analysis. The results show that the IRC research has gone through three phases, namely, “emergence” (1957–1991), “fermentation” (1992–2005) and “take-off” (2006–2015) phases. The co-citation network analysis confirms that the IRC research field has been developed under the influence of two pioneering studies related to bibliometrics research. The main research trajectories in IRC studies over the three development phases and over the whole period are identified based on the main path analysis, which shows that co-authorship analysis is the main research method in IRC studies. A bibliographic coupling analysis suggests that the whole IRC research domain can be classified into five distinct intellectual areas: drivers of IRC, IRC patterns, IRC effects, IRC networks and IRC measurement. Seven topics for future research are also identified.